Green Economy and Some Relevancies from Islamic Finance Perspective - Aam; Muhammad (SMART Insight, 2022)
The green economy is one of the new economic concepts still popular in research, emphasizing the balance between economic and environmental dimensions. The green economy concept is in line with the existing concept of Islamic finance. As a new concept, research related to a green economy is also developing. Therefore, this study aims to provide qualitative information on the development of green economy literature. There are 1183 papers in journal articles, book chapters, and conference papers indexed by the Scopus database from 1961-2021. We employed VOSViewer and Excel software to synthesize and analyze the data. This research is limited to the Scopus database related to the green economy. In addition, we identified the relevancies between the green economy and Islamic finance, and some research has been discussed these issues. Regarding the result obtained, we found that the rules in Islamic finance support the implementation of the green economy concept. Furthermore, we also found sukuk as a potential instrument in Islamic finance that can be utilized to promotes the green economy concept.